2002
DOI: 10.1007/s11745-002-0943-x
|View full text |Cite
|
Sign up to set email alerts
|

Action of 1‐(11‐selenadodecyl)‐glycerol and 1‐(11‐selenadodecyl)‐3‐trolox‐glycerol against lipid peroxidation

Abstract: The antioxidant action on lipid peroxidation of the synthesized selenium compounds 1-(11-selenadodecyl)-glycerol (SeG) and 1-(11-selenadodecyl)-3-Trolox-glycerol (SeTrG, where Trolox = 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) was investigated. We compared the reactivity of the selenium compounds toward peroxyl radicals and their inhibitory effect on lipid peroxidation, induced by several kinds of initiating species such as azo compounds, metal ions, and superoxide/nitric oxide in solution, micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The ability of gallic acid to protect tocopherols has been documented in many papers (Kajimoto et al 1988a(Kajimoto et al ,b, 1990a(Kajimoto et al ,b, 1991a, under various conditions, including frying (Kajimoto et al 1988a(Kajimoto et al , 1990a(Kajimoto et al ,b, 1991a. The ability of caffeic acid to protect tocopherols has also been reported previously (Ochi et al 1994;Raneva et al 2001Raneva et al , 2002Pazos et al 2005a), although the ability of this phenolic acid to protect tocopherols has not yet been studied during frying. However, it has been reported that protocatechuic acid is able to protect α-tocopherol (during oxidation of human LDL lipoproteins in vitro) (Zhang et al 2001), although it did not protect α-tocopherol in the present study.…”
Section: Resultssupporting
confidence: 57%
“…The ability of gallic acid to protect tocopherols has been documented in many papers (Kajimoto et al 1988a(Kajimoto et al ,b, 1990a(Kajimoto et al ,b, 1991a, under various conditions, including frying (Kajimoto et al 1988a(Kajimoto et al , 1990a(Kajimoto et al ,b, 1991a. The ability of caffeic acid to protect tocopherols has also been reported previously (Ochi et al 1994;Raneva et al 2001Raneva et al , 2002Pazos et al 2005a), although the ability of this phenolic acid to protect tocopherols has not yet been studied during frying. However, it has been reported that protocatechuic acid is able to protect α-tocopherol (during oxidation of human LDL lipoproteins in vitro) (Zhang et al 2001), although it did not protect α-tocopherol in the present study.…”
Section: Resultssupporting
confidence: 57%
“…1A and 1B) competing with a-tocopherol to scavenge the hydrophilic and lipophilic radicals. Previously we have shown that tocotrienols, added exogenously to rat plasma, oxidized by AAPH, spared atocopherol consumption (13). In SIN-1 oxidation tocotrienols and astaxanthin used together have the best sparing effect on a-tocopherol consumption, tocotrienols do not protect a-tocopherol, and astaxanthin increased the rate of consumption of a-tocopherol (Fig.…”
Section: Interaction Between A-tocopherol Tocotrienols and Astaxanthmentioning
confidence: 80%
“…anthin Determination a-Tocopherol, tocotrienols and astaxanthin were extracted as described in (13). A volume of 20 mL of the extracted lipids in hexane solution was injected into the column of the HPLC system with a fluorescence detector (Shimadzu Corp., Kyoto, Japan) for the determination of a-tocopherol and tocotrienols.…”
Section: A-tocopherol Tocotrienols and Astax-mentioning
confidence: 99%
“…Apart from being an integral part of GSH-Px, Se can antagonize the toxic effects of some chemical substances (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%